An innovative state-of-the-art health storytelling technique for better management of type 2 diabetes - Ali, Sumbal; Bakht, Shumaila; Ullah Jan, Atta; Alam, Iftikhar; Almajwal, Ali Madi; Osaili, Tareq; Obaid, Reyad Shakir; Faris, MoezAllslam Ezzat; Cheikh Ismail, Leila; Najah, Farah; Radwan, Hadia; Hasan, Haydar; et al. (Frontiers in Public Health, 2023)
Background: Type-2 Diabetes (T2D) is a life-long chronic disease that needs long-term prevention and management strategies in a community setting. A health story is a new technique that may be used as an effective tool for better prevention and management of T2D.The main objective of this study is to develop a story to be used as a social healthtechnique based on contemporary scientific knowledge that may be used on a community level for better communication and management of T2D.Methods: A community-academic partnership was agreed upon with a non-for-profit Nutrition Education, Awareness, and Training (NEAT) organization Khyber Pakhtunkhwa, Pakistan. We agreed to develop a story that may be used as a health and nutrition education communion tool for better management of patients with T2D. The following phases were followed during the story creation process: (1) Theory Phase, (2) Modeling Phase, and (3) Evaluation Phase. Raters evaluated the story to determine its literary and scientific quality, comprehensiveness, and T2D specificity.The title of the story translated in English is "the story of Diabetes -the story of Success". This is a text-based 86 pages long in the local language "Pashto" with an English translation. The story is divided in five chapters and describes initial diagnosis, fear associated with the disease, issues related to referral to certified practitioners, importance of balanced diet and related lifestyle habits. After story evaluation, the raters suggested its literary and scientific quality, comprehensiveness, and T2D specificity (Pearson Correlation scores of >0.8).This unique story was created for T2D and found to be of significant quality in terms of its literary and scientific quality, as well as its comprehensiveness and diabetes-specificity. As a result, it may be suggested that it can be used in subsequent studies to improve T2D management among adult patients.